Study on the bone mineral density of broiler suffering femoral joint degenerative lesions - Paz, Ibiara Correia de Lima Almeida [UNESP]; Mendes, Ariel Antonio [UNESP]; Balog, Augusto [UNESP]; Vulcano, Luiz Carlos [UNESP]; Ballarin, Adriano Wagner [UNESP]; Almeida, I. C. L. [UNESP]; Takahashi, S. E. [UNESP]; Komiyama, C. M. [UNESP]; Silva, M. C. [UNESP]; Cardoso, K. F. G. [UNESP] (Fundação APINCO de Ciência e Tecnologia Avícolas, 2008)
An experiment was carried out with male and females broilers of two different commercial breeds to evaluate bone mineral density of the right femur head. A number of 600 one-day-old broilers were raised in an experimental poultry house up to 42 days of age at the School of Veterinary Medicine and Animal Science of UNESP, Botucatu, Brazil. After slaughter, three males and three females in each breed in each of the established gross scores were selected. Their femora heads were submitted to gross examination, and subsequently the thighs were submitted to the Veterinary Hospital for radiographic analysis. Femora were also submitted to bone resistance, Seedor index, and dry matter content analyses. All these bone quality characteristics were different between males and females, independent of breed. Breeds presented similar behavior. It was possible to establish correlations between bone quality parameters, and confidence intervals for bone mineral density values, correlating them to femoral degeneration score, which allows characterizing femoral head lesions by radiographic optical densitometry.
Keywords: Bone mineral density; broilers; femoral degeneration; femur; genetics